The Knowledge-Evolving Project: Fundamentals to a Complete Project Knowledge Management Discipline - Al Marri, Khalid (2022)
This paper establishes a knowledge management doctrine unique to the f ield of project management. The paper investigates and expands on the theoret ical frameworks and practices of organisational knowledge management – which is the dominate doctrine in the discipline of knowledge management – to deduce a theory and a practice of project knowledge management that is distinctive from other knowledge management fields. It is discovered that the knowledge dynamics at the foundational level of project knowledge management is a symmetrical transposition of that of organisational knowledge management. Thus, the Knowledge-Evolving Project doctrine is established as the inverse of the Knowledge-Creating Company. Exploring a knowledge management discipline distinctive to project management inevitably leads to new insights that are potentially significant to managing knowl edge in projects in particular and to knowledge management discipline in general. Most of the current literature on project knowledge management is almost indistin guishable from organisational knowledge management. The very same theoretical and empirical concepts and ideas are applied interchangeably in both management f ields. This paper takes the rare step of creating a new theory and practice of project knowledge management such that it is distinctive from other knowledge management f ields.